The role of imagination in the creation of transnational subjectivities in Bharati Mukherjee`s "Leave It To Me" - Filipczak, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article draws on Arjun Appadurai`s theory of the power of imagination in modern life expressed in his book "Modernity at Large" (1996). In his attempt to capture the chaotic character of globalization, which he identifies as five different flows, or "scapes", Appadurai notices that the flows are mutually constitutive, while migrations and circulation of the media images, so ethnoscapes and mediascapes respectively, affect human imagination and, in the result, shape modern subjectivities.
Keywords: globalization; imagination; agency; transnational identities; imagined communities